Six years of experience in entomological surveillance of indoor residual spraying against malaria transmission in Benin: lessons learned, challenges and outlooks - Akogbéto, Martin; Aïkpon, Rock; Azondekon, Roseric; Padonou, Gil G.; Ossè, Razaki A.; Agossa, Fiacre R.; Beach, Raymond; SEZONLIN, MICHEL (My University, 2015)
Background: From 2008 to 2013, a prevention intervention against malaria based on indoor residual spraying (IRS) was implemented in Benin. From 2008 to 2012, Ficam M®, a bendiocarb-containing product was used for house spraying, in association with pirimiphos methyl EC (Actellic EC) in 2013. This operation aimed to strengthen the effectiveness of treated nets so as to expedite the achievement of Millennium Development Goals (MDGs): the reduction of morbidity and mortality due to malaria by 75 % from 2000 to 2015. Methods: Monitoring and evaluation (M&E) was implemented in order to evaluate the impact of IRS intervention on malaria transmission. Anopheles gambiae s.l. populations were sampled by human landing catch. In addition, window exit traps and pyrethrum spray catches were performed to assess exophagic behaviour of Anopheles vectors the main malaria vector in the treated areas. The residual activity of insecticide in the treated walls was also assessed using WHO bioassay test. Results: The purpose of this project was to draw attention to new challenges and future prospects for the success of IRS in Benin. The main strength of the intervention was a large-scale operation in which more than 80 % of the houses were treated due to the strong adhesion of population. In addition, a significant reduction of the EIR in areas under IRS were observed. However, there were many challenges including the high cost of IRS implementation and the identification of suitable areas to implement IRS. This was because of the low and short residual effect of the insecticides recommended for IRS and the management strategy for vector resistance to insecticides. This indicated that challenges are accompanied by suggested solutions. For the cost of IRS to be accessible to states, then local organizations need to be created in partnership with the National Malaria Control Programme (NMCP) in order to ensure relevant planning and implementation of IRS. Conclusion: As an anticipatory measure against vector resistance, this paper proposes various methods, such as periodic IRS based on a combination of two or three insecticides of different classes used in rotation every two or three years.
Keywords: Indoor residual spraying; Lessons learned; Benin